3D printed textile and fashion - Aniqa Ansari
The fashion industry is known for its evolving trends and innovations, and the ever-increasing demand for new designs and developmental techniques. Over the years, printing and designing methods have been developed and upgraded to overcome the traditional production and designing techniques. The innovation of 3D printing eases the designers' work in making a whole new design frame and production process. 3D printing, which is also known as additive manufacturing, involves making three-dimensional objects based on computer-aided design to physical objects, adding the material layer-by-layer. It allows designers to innovate faster and gives flexibility to create new designs. As the manufacturing process of textiles and fabrics leads to water and air pollution and wastage of material, 3D printing can address many of these issues. This review explores the uses and implementation of 3D printing in textiles and fashion, examining various printing technologies, materials, design methodologies, and practical applications. It also focuses on the challenges faced in adopting 3D printing technology.